A Study On Stress Management Among Employees Working In Auto Components Industries - R. Suresh; Arhan Athapit; M.Jaya Prakash; M.Jaya Prakash; Radhika S (Elementary Education Online, 2023)
The main aim of this study is to identify the stress management among employees working in selected Auto components manufacturing Industries in Chennai. The study was conducted to identify the causes of stress, the symptoms experience by the employees, and how the organization is effectively in handling the stress of the employees in the day to day working environment. The research adopts a survey approach where self-administered questionnaires were issue to gather data from the employees to measure their opinion regarding stress management. The data is collected through both primary and secondary data. In primary data a questionnaire has been framed and collected from 120 respondents, books, journals, websites are referred as secondary data. The statistical tools used under the study are one way ANOVA, chisquare test, Henry Garrett Ranking method, mean and standard deviation and H-test. It can be concluded that meeting target and workload are some of the major causes of stress, It was found that tension; headache is some of the symptoms caused due to stress. Organization is effective in handling the stress management practices. By engaging employees in effective training and employee assistance program helps to manage their stress and through healthy compensation plans and performance based incentives lead the employees to work effectively.